2010
DOI: 10.1186/1757-1146-3-29
|View full text |Cite
|
Sign up to set email alerts
|

Foot posture in people with medial compartment knee osteoarthritis

Abstract: BackgroundFoot posture has long been considered to contribute to the development of lower limb musculoskeletal conditions as it may alter the mechanical alignment and dynamic function of the lower limb. This study compared foot posture in people with and without medial compartment knee osteoarthritis (OA) using a range of clinical foot measures. The reliability of the foot measures was also assessed.MethodsThe foot posture of 32 patients with clinically and radiographically-confirmed OA predominantly in the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
123
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(135 citation statements)
references
References 52 publications
6
123
2
4
Order By: Relevance
“…However, this difference was due to greater eversion excursion during initial contact rather than during midstance or propulsion as in our study. Other studies that used different reference positions to ours report inconsistent results, with two finding greater peak eversion in pes planus [3,21] compared to three that found no significant differences [8,26,27].…”
Section: Discussioncontrasting
confidence: 70%
“…However, this difference was due to greater eversion excursion during initial contact rather than during midstance or propulsion as in our study. Other studies that used different reference positions to ours report inconsistent results, with two finding greater peak eversion in pes planus [3,21] compared to three that found no significant differences [8,26,27].…”
Section: Discussioncontrasting
confidence: 70%
“…Research has shown that medial knee OA is associated with a flattened (pronated) foot posture [50]. Furthermore, recent data has linked the pronated foot type to a greater frequency of knee pain and medial tibiofemoral cartilage damage in older people [51].…”
Section: Role Of Footwear and Insoles In The Management Of Knee Oamentioning
confidence: 99%
“…Las ortesis plantares constituyen un elemento terapéutico ampliamente utilizado para intentar corregir esta desalineación de los segmentos que conforman el miembro inferior 2,3,[5][6][7][8][11][12][13][14][15][16] . Su uso se basa en el control de la movilidad subtalar tanto a nivel del rango articular como a nivel de la velocidad del movimiento 5 .…”
Section: Introductionunclassified
“…Varios investigadores han descubierto en sus estudios 14,15 que con el uso de ortesis plantares hay diferencias significativas en los movimientos que conforman los segmentos del miembro inferior y explicarían así la mejoría en cuanto a la sintomatología dolorosa. Pero por otro lado, existen otras investigaciones 3,7,16 que no han demostrado que la disminución de la sintomatología dolorosa se deba a una corrección de la alineación de los segmentos que conforman el miembro inferior dado que el uso de las ortesis plantares no produce movimientos significativos en dichos segmentos.…”
Section: Introductionunclassified
See 1 more Smart Citation